Quantitative methods for business and management - Buglear, John (Pearson, 2012)
Quantitative Methods for Business and Management Students takes you on a journey though the techniques required to succeed in business and management. With a user-friendly and accessible writing style, John Buglear presents these techniques simply and provides numerous examples to enable you to relate the theory to real-life applications
Keywords: kvantitativní metody; matematická ekonomie; quantitative methods; mathematical economics; učebnice vysokých škol; textbooks (higher)